Optimal goal programming of softgoals in goal-oriented requirements engineering - Subramanian, C.; Krishna, Aneesh; Kaur, Arshinder (2016)
Non-functional or quality requirements such as usability, integrity and security play a significant part in the success of a software system. Non-functional requirements have more impact on software systems than the functional requirements. In the early phase of requirements engineering, the various design options for the functional behaviour (also known as the goal) of a software system are analysed and the perfect ones are chosen. In the goal analysis process, the goals that contribute to the maximum satisfaction of the non-functional requirements (also known as the softgoals) have to be selected. Whilst there have been a number of approaches for goal analysis, this paper focuses on the softgoals based optimisation model to select goals for a given i* framework. This paper presents a multi-objective goal programming optimisation model to guide the goal analysis. A simulation for this approach was developed in Java Eclipse integrated with the IBM Cplex optimisation tool and evaluated with goal models such as Telemedicine, and Kids Youth counseling which were taken from the Requirements Engineering (RE) literature. The results of the evaluation show that the proposed optimal goal model approach is beneficial in the decision making of functional goals.